Elasticity‐Dependent Fast Underwater Adhesion Demonstrated by Macroscopic Supramolecular Assembly. Issue 29 (19th June 2018) - Ju, Guannan; Cheng, Mengjiao; Guo, Fengli; Zhang, Qian; Shi, Feng
Abstract: Macroscopic supramolecular assembly (MSA) is a recent development in supramolecular chemistry to associate visible building blocks through non‐covalent interactions in a multivalent manner. Although various substrates (e.g. hydrogels, rigid materials) have been used, a general design rule of building blocks in MSA systems and interpretation of the assembly mechanism are lacking and are required. Herein we design three model systems with varied elastic modulus and correlated the MSA probability with the elasticity. Based on the effects of substrate deformability on multivalency, we have proposed an elastic‐modulus‐dependent rule that building blocks below a critical modulus of 2.5 MPa can achieve MSA for the used host/guest system. Moreover, this MSA rule applies well to the design of materials for fast underwater adhesion: Soft substrates (0.5 MPa) can achieve underwater adhesion within 10 s with one order of magnitude higher strength than that of rigid substrates (2.5 MPa). Abstract : Elastic fantastic : Macroscopic supramolecular assembly (MSA) provides an ideal model to study interfacial interactive phenomena between large surfaces. Using hydrogels, the MSA probability is correlated with the substrate deformability based on the statistical results of MSA and in situ quantification of interactive forces. This elastic‐modulus‐dependence rule is shown to be applicable to the design of underwater adhesion systems.